2005
DOI: 10.1007/s11270-005-0722-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Eisenia foetida for Sustainable and Efficient Vermicomposting of Fly Ash

Abstract: Vermicomposting of fly ash has been attempted, using red earthworm, Eisenia foetida. Fly ash, which was obtained from thermal power station, was mixed with cowdung in different proportions (20, 40, 60 and 80%). These mixtures were used as feed for earthworms, and after 30 days, vermicast recovery, worm zoomass and numbers of juveniles produced were recorded. A total of six runs each of 30 days were conducted during the whole study. Concentrations of heavy metals in different mixtures of fly ash-cowdung, before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 9 publications
3
28
0
3
Order By: Relevance
“…This signified that the abattoir soils in this study contained higher levels of heavy metals than the control site soil. This agreed with the work of Gupta, Tewari, Srivastava, Murthy, and Chandra (2005), who reported that earthworm tissue metal level is directly related to their proportion in a given soil. Similar pattern of metal bioaccumulation was observed by Suthar, Singh, and Dhawan (2008).…”
Section: Discussionsupporting
confidence: 92%
“…This signified that the abattoir soils in this study contained higher levels of heavy metals than the control site soil. This agreed with the work of Gupta, Tewari, Srivastava, Murthy, and Chandra (2005), who reported that earthworm tissue metal level is directly related to their proportion in a given soil. Similar pattern of metal bioaccumulation was observed by Suthar, Singh, and Dhawan (2008).…”
Section: Discussionsupporting
confidence: 92%
“…Some of the metals accumulated in body tissues and some was likely lost through leaching. Previous studies have revealed that earthworms can accumulate heavy metals in their tissues during the process of vermicomposting (Hartenstein and Hartenstein 1981;Graff 1982;Garg and Kaushik 2005;Gupta et al 2005). Garg and Kaushik (2005) reported a considerable loss in heavy metal contents from solid textile mill sludge mixed with poultry droppings.…”
Section: Resultsmentioning
confidence: 99%
“…They attributed the heavy metal loss from substrate to accumulation by earthworm body tissues. Gupta et al (2005) studied the vermicomposting of fly ash by mixing it with cow dung in different ratios and reported 30-50% loss in heavy metal content in different combination, at the end. They reported that heavy metals bioaccumulated in earthworm tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, higher concentrations of heavy metals may affect the growth and reproduction of African Nightcrawler earthworms. Previous studies have revealed that earthworms can accumulate heavy metals in their tissues if reared in contaminated soils for long periods (Gupta et al 2005;Suthar 2008). …”
Section: Heavy Metal Concentration In Vermicompostmentioning
confidence: 99%